A Rhetorical Analysis of the Elevator Pitch - Vasev, Mariyan (Media and Language, 2020)
The elevator pitch (also known as elevator speech) is a widely used communication tool in a business context. The elevator pitch is a micropresentation: a short, direct, engaging and approachable speech, specifically adapted to the audience and the situation in which it is delivered. The current article reviews the persuasive characteristics of the elevator speech through the prism of the science of Rhetoric. The text emphasizes the different types of arguments used in an elevator speech, together with the characteristics of nonverbal communication to make an elevator pitch persuasive and effective.